2016
DOI: 10.15171/jrip.2016.01
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement; a kidney’s perspective

Abstract: Transcatheter aortic valve replacement (TAVR) has now emerged as a viable treatment option for high-risk patients with severe aortic stenosis (AS) who are not suitable candidates for surgical aortic valve replacement (SAVR). Despite encouraging published outcomes, acute kidney injury (AKI) is common and lowers the survival of patients after TAVR. The pathogenesis of AKI after TAVR is multifactorial including TAVR specific factors such as the use of contrast agents, hypotension during rapid pacing, and emboliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 67 publications
1
45
0
Order By: Relevance
“…To date, more than 200,000 TAVR procedures have been performed [6, 7]. Although TAVR is considered a less invasive treatment compared with SAVR, the one and two year mortality following TAVR is still considerable at 24% and 34%, respectively [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 200,000 TAVR procedures have been performed [6, 7]. Although TAVR is considered a less invasive treatment compared with SAVR, the one and two year mortality following TAVR is still considerable at 24% and 34%, respectively [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the recently published studies also suggest that patient selection for TAVR is evolving toward treating lower surgical risk patients (7)(8)(9). Thus, to date, more than 200 000 TAVR procedures have been performed worldwide (3,10). Despite increasing evidence of treating intermediate surgical-risk patients (7)(8)(9), many patients elected for TAVR commonly have renal insufficiency (11,12), one of important predictors for acute kidney injury (AKI) development (13).…”
Section: Introductionmentioning
confidence: 99%
“…Despite increasing evidence of treating intermediate surgical-risk patients (7)(8)(9), many patients elected for TAVR commonly have renal insufficiency (11,12), one of important predictors for acute kidney injury (AKI) development (13). In addition, AKI following TAVR is very prevalent, varying from 15% up to 57% (10,11,(14)(15)(16). Although patients with chronic kidney disease (CKD) carry a higher risk of developing AKI, improvement in estimated glomerular filtration rate (eGFR) following surgical aortic valve replacements (SAVRs) has been demonstrated in patients with CKD after relief of severe aortic valve diseases (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of transcatheter aortic valve replacement (TAVR), we recently performed a comprehensive review of available data on incidence and risk factors of AKI after TAVR (3). We demonstrated that causes of AKI following TAVR are likely multifactorial including hypotension during rapid ventricular pacing for balloon valvuloplasty and valve deployment, use of contrast agents, and embolization resulting from the manipulation of catheters in the aorta of patients with diffuse atherosclerosis (4-6).…”
Section: Dear Editormentioning
confidence: 99%